ANALYSIS OF LOCAL CLINICAL FACTORS THAT AFFECT THE EFFECTIVENESS OF MANDIBULAR ANESTHESIA - Anisimov, M.V.; Shnaider, S.A.; Anisimova, L.V.; Sennikov, O.M.; Babenia, H.O. (World of Medicine and Biology, 2022)
For the treatment of mandibular teeth in adult patients, mandibular anesthesia is used in more than 80 % of cases. The method of SN Weisblat (in domestic literature or inferior alveolar nerve block - AB - in foreign literature) is the most frequently used, but rather difficult in terms of variability of reference points. We have proposed the Back Low technique, in which the needle is located behind the alveolar part of the mandible in the projection of the anterior margin of the coronal process, and the target point in this technique will be in the lower pterygomandibular spaces and 1 cm below the mandibular foramen. Clinical observations indicate that even a small violation of the technique has a critical effect on its efficacy. The purpose of our work is to determine local factors, study their frequency and their influence degree on the clinical efficacy of mandibular anesthesia in different techniques. The study involved 2,000 patients aged 18 to 65 years. Based on clinical studies, it was found that the factors that complicate carrying out mandibular anesthesia include small mouth opening (2.30 %), increased gag reflex (4.60 %), features of the structure and location of the tongue, as well as its mobility during anesthesia (7.55 %). Based on the analysis of the index of mandibular anesthesia (IMA), a decrease was found in the efficacy of mandibular anesthesia in the observed adverse factors, regardless of the technique of its implementation. Mandibular anesthesia in the Back Low technique showed higher efficacy in patients without complicating anesthesia factors – by 38 %; with a small opening of the mouth – by 47 %; with the urge to vomit – by 40 %; with “interfering” tongue – by 14 %, which makes her choice better.